Cinema e filosofia : Um estudo da narrativa cinematográfica maranhense das Jornadas por meio da tríplice mímesis - COSTA, Alexandre Bruno Gouveia (2015)
This dissertation results of research on the Maranhão audiovisual production comprising the late 70's and part of the 80s, for we include production in Super-8 and 16mm, respectively: Periquito Sujo (1979), Greve da meia passagem (1979-1980), Quem matou Elias Zí? (1986), Bandeiras Verdes (1988) in order to investigate the potential for communicability and representativeness of these works to maintain a cinematic identify from the methodology based on the triple mimesis and construction of narrative identities. Empirical research framework Maranhão film works are awarded on the issues of cinematrographic Days, important movement for the construction and maintenance of Maranhão cinematic narrative identify. From the triple mimesis concept endorsed by Paul Ricoeur (2012), you can understand how filmic narratives that pass for ethical reasons, begin in broader terms of social and cultural environment insertion of the events narrated and only complete in the times of reading, this visual event, with effective participation of the viewer.